Evaluation of Detect-A-Strep and the Culturette Ten-Minute Strep ID kits for detection of group A streptococcal antigen in oropharyngeal swabs from children. - Campos, J M (1985)
The Detect-A-Strep kit (DAS) (Antibodies Inc.) and the Culturette Brand 10-Minute Group A Strep ID kit (CBTMSI) (Marion Scientific) were compared with a sensitive culture method for detection of group A streptococci in oropharyngeal swabs from children. Specimens from 953 children ranging in age from 4 months to 18 years were inoculated to selective blood agar plates containing sulfamethoxazole-trimethoprim. Culture plates were incubated anaerobically for the first overnight period and aerobically in the presence of 10% CO2 for the second overnight period. The same specimens were tested within 24 h by DAS (phase 1) or CBTMSI (phase 2). One hundred thirty-five of 538 specimens (25.1%) tested by DAS and 150 of 415 specimens (36.1%) tested by CBTMSI were culture positive. DAS detected 87 of 135 (64.4%) and CBTMSI detected 93 of 150 (62.0%) culture-positive specimens. The specificities of DAS and CBTMSI were 96.5 and 99.6%, respectively. The predictive values of positive and negative results were 86.1 and 89.0% for DAS and 98.9 and 82.2% for CBTMSI. Because a reliable distinction between infected patients and carrier state patients cannot be made, we conclude that neither DAS nor CBTMSI is sufficiently sensitive to replace our culture method.